2012
DOI: 10.1016/j.cub.2012.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary Centrosomes Nucleate Extra Cilia and Compromise Primary Cilium Signaling

Abstract: Summary The primary cilium is a nexus of cell signaling, and ciliary dysfunction is associated with polycystic kidney disease, retinal degeneration, polydactyly, neural tube defects, and obesity (ciliopathies) [1]. Signaling molecules for cilium-associated pathways are concentrated in the cilium, and this is essential for efficient signaling. Cilia are nucleated from centrioles, and aberrant centriole numbers are seen in many cancers and in some ciliopathies [2]. We tested the effect of supernumerary centriole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 29 publications
12
98
0
1
Order By: Relevance
“…We occasionally observed multiple cilia after irradiation, often emerging side by side, possibly from a single ciliary pocket, as has been observed recently, where multiple cilia were formed after Plk4 overexpression induced supernumerary centrioles. 42 These multiple cilia only ever grew from mature centrioles, as confirmed by cenexin staining (Fig. 3B).…”
Section: Discussionmentioning
confidence: 89%
“…We occasionally observed multiple cilia after irradiation, often emerging side by side, possibly from a single ciliary pocket, as has been observed recently, where multiple cilia were formed after Plk4 overexpression induced supernumerary centrioles. 42 These multiple cilia only ever grew from mature centrioles, as confirmed by cenexin staining (Fig. 3B).…”
Section: Discussionmentioning
confidence: 89%
“…Increasing chemical activities by concentrating molecules in cilia constitutes an attractive hypothesis for how cilia could participate in signalling. Indeed, Mahjoub & Stearns [11] found that diluting Hedgehog signalling intermediates into multiple primary cilia decreased pathway activation. An alternative model views cilia as the assembly point for specific scaffolds that bring together entire signalling modules in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical aberrations in centrosome numbers have been demonstrated to alter ciliary signaling and have been proposed to be the underlying cause for certain defects in tissue organization (7,8). In addition, recent genetic studies on the master regulator of centrosome number, polo-like kinase 4 (PLK4), have shown that, whether too few or too many, perturbations in centrosome numbers can directly impede brain development, leading to microcephaly both in mice and in humans (9,10).…”
mentioning
confidence: 99%